Electroexcitation of giant resonances in ⁵⁴Fe and ⁵⁶Fe nuclei - Khvastunov, V.M.; Denyak, V.V.; Ranyuk, Yu.N. (Вопросы атомной науки и техники, 2004)
The investigation of giant multipole resonanсes in ⁵⁴Fe and ⁵⁶Fe nuclei has been carried out. The resonance at excitation energy of~13 MeV (51A¹/³) is shown to be of E2 type and to exist in both nuclei. In both nuclei the contribution of the E3 multipole is very small, especially of the 1 -ω branch of isovector resonance, and the E4 resonance is absent completely. Small E5 strength contribution is observed in both nuclei at excitation energy of 10 to 15 MeV.